Non-invasive multimodality cardiac stress test imaging: Role of echocardiography, cardiac computed tomography, cardiac magnetic resonance, and nuclear medicine - Kahadi, Cik; Handari, Saskia Dyah (Heart Science Journal, 2025)
Coronary artery disease, or CAD, is the major cause of mortality and morbidity globally, with significant socioeconomic impact. Based on European Society of Cardiology or ESC guidelines in Chronic Coronary Syndrome (CCS), multimodality imaging strategies are highly suggested in evaluating the patient who suspected CAD. Non-invasive imaging modalities can assess the anatomy of coronary artery by using Coronary Computed Tomography Angiography (CCTA) or assess functional stress testing with inducible myocardial ischemia by using Stress Echocardiography (SE), Myocardial CT Perfusion (CTP), Cardiac Magnetic Resonance (CMR), Single Photon Emission Computed Tomography (SPECT), or Positron Emission Tomography (PET). Nowadays, it’s important to recognize the limitations and capabilities of each imaging method, especially before selecting a functional testing focused on ischemia compared to an anatomy of coronary imaging. This paper describes an overview of non-invasive imaging modalities for the general diagnosis of CAD patients. Non-invasive multimodality cardiac stress test imaging is enhancing the diagnosis of significant stenosis of the coronary artery. Understanding the benefits and limits of each imaging is essential for determining the best modality we used.